ANALISIS GAYA KEPEMIMPINAN DALAM MENINGKATKAN KINERJA KARYAWAN PT DANA PENSIUN JIWASRAYA (DPPK) JAKARTA PUSAT - Frastiyono, Dhanis; Nariah (Journal of Research and Publication Innovation, 2024)
The aim of this research is to analyze leadership styles in improving the performance of PT Dana Pensiun Jiwasraya employees. The research method used in the research is a qualitative descriptive method and the research instruments used are observation, interviews, documentation. The results of the research show that the leadership style in improving the performance of employees at PT Dana Pensiun Jiwasraya applies a transformational leadership style, seen from the leader making decisions according to his beliefs, but without prior discussion with the employees, it is contradictory to the employees and the impact of these results can be seen from the performance indicators, namely quality, quantity, responsibility, cooperation, initiative from these five indicators, many employees complain that the portion of responsibility is very heavy due to excessive work.